Pengaruh Pembelajaran Geoboard Terhadap Hasil Belajar Siswa Pada Pembelajaran Matematika Kelas V SDN 101746 Klumpang Kebun Tahun Ajaran 2023/2024 - Ade Mufidah; Astria Ayu Ramadianti; Emy Hariati (Pentagon : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
The problems in this study are the lack of students' ability to understand the lessons given, the results of the Mathematics learning exam that have not reached the KKM, and the teacher has not applied various innovative media. This study aims to determine the effect of learning outcomes of class V students of SDN 101746 Klumpang Kebun in learning Mathematics on flat shape material using Geoboard learning media, which consists of two classes. The researcher took class V A and class V B to be used as samples totaling 24 people as the experimental class and 22 people as the control class. The type of research used in this study is quantitative quasi-experimental (Quasi Experimental Design). The design in this study is Nonequivalent Control Group Design, this design the experimental group and the control group are not selected randomly. Data collection techniques with observation, testing and documentation. After the pretest ability is obtained, the next step is to conduct learning with Geoboard learning media for class V. So that the posttest ability is obtained in the experimental class students with an average learning outcome of 88 and the control class 74. It is clear that the increase in the experimental post-test score is on average higher than the control class. After the pre-test and post-test values ​​are known, a hypothesis test is carried out using the t-test. The basis for taking the independent t-test at the sig level (2-tailed) of 0.01 <0.05, which means that the hypothesis is accepted, namely that there is an influence of the use of Geoboard learning media on the learning outcomes of mathematics on flat building material for grade V students of SDN 101746 Klumpang Kebun.